Przekład wobec oryginału. Różne czasy, różne style - Sławkowa, Ewa (Stylistyka, 2021)
Postulating the necessity of introducing translatological reflection into modem stylisti- cs, the article - bearing upon the work of Polish translators of Charles Baudelaire’s poems - demonstrates a diversity of stylistics strategies in particular translations. The texts cho- sen for the study Correspondences, De Profundis Clamavi, and Les Plaintes d’un Icare have been rendered into Polish by both older (Stanisław Korab-Brzozowski, Miriam, and Antoni Lange), and modem (Tadeusz Bocheński, Maria Leśniewska, Andrzej Nowak) translators. A comparative study of the French originals and their Polish equivalents car- ried out with the help of cognitive grammar analysis allows us to conclude that neither the very time nor the style of translation determine its value in the target language culture. This awareness becomes important particularly in the light of a discussion conceming ca- nons of French and European literatures.